Socio-Historic Contexts of Sino-Nigerian Relations in Infrastructure Development in Nigeria - Fajobi, Tolulope Adetayo (Journal of Contemporary International Relations and Diplomacy, 2026)
The emergence of Sino-Nigerian relations in the Nigerian economy, can be attributed to the Military Government that strategically brought the Chinese closer to Nigeria for economic transformation. This action is intended to fill the gap created by the isolation of the country by the United States and her Western allies as a result of political crisis in Nigeria especially in 1990’s. Consequently, despite the cooperation from China, through Sino-Nigerian partnership, there is uncertainty surrounding the level of relations between the two countries in terms of infrastructure development. This is due largely to the antecedent of the Chinese economic interactions in some countries in Africa where most of the benefits were more of advantages to China. The study assessed the context of transportation diplomacy between China and Nigeria, and also examined the enthusiasm behind the Sino-Nigerian partnership in transportation infrastructure modernization in Nigeria. The study engaged descriptive research design through qualitative approach, which relied on interviews and secondary data. The study concluded that Sino-Nigerian relations is laudable, the sustainability outcomes of the relationship remain a major concern because of historical antecedents of relationship termination between the two countries. The study also discovered that of a lack of transparency on the part of the Nigerian government, based on the fact that highly placed Nigerian officials from successive governments to the present governments have no first-hand knowledge of the terms and conditions of China-Nigeria relations, especially in railway-related matters. Although, the study identified that the Sino-Nigerian relationship has yielded infrastructural developments with special focus on railway projects, however, this has not translated into human development in terms of job creation and improved standard of living. The study, therefore, recommends that there is need deliberate policy safeguards, mutual trust, and lessons drawn from past experiences to ensure continuity, accountability, and sustainable development outcomes.